(untitled) (MAUSAM, 1966)
The Lahaul and Spiti valley in the Punjab Himalayas experienced a spell of severe snowfall in the third week of September 1962. This was unusually early for the area. The synoptic features which led to this situation have been described in this paper. The interesting point revealed in the present study is that the cold air outbreak from an anticyclone moving east and southwest from Ukrainian area in synchronization with the recurvature of the monsoon depression was the main cause of the snowstorm. The probable influence of the Urals has also been indicated.